Social Protection Programs and Their Support for Promoting Access to Nutrient-Dense Foods for Vulnerable Communities in South Africa - Tendaiishe Berejena; Florence Malongane; Thokozile Ingrid Metsing (Current Developments in Nutrition)
Social protection programs (SPPs) have been established to tackle challenges from economic downturns, conflicts, and the impacts of global warming, with women and children being particularly vulnerable during these times. Programs like Child Support Grants (CSG), the Old People’s Grant (OPG), the National School Nutrition Programme (NSNP), Food Parcels, Food Fortification Programmes (FFP), and Nutrition Sensitive Agriculture (NSA) show promise in alleviating food insecurity and improving nutritional health. This review assessed key SPPs in South Africa, focusing on their support of access to nutrient-dense food provision for vulnerable communities. A comprehensive literature search was conducted using databases like PubMed, Google Scholar, and Medline to evaluate the success of these programs. The Academy of Nutrition and Dietetics Quality Criteria Checklist was employed to systematically evaluate and assess the quality of each study. The narrative review assessed 6 key SPPs offered by the government, with 4 failing to provide access to nutrient-dense foods, especially for women and children. Only 2 programs meet this nutritional objective. The NSA and the FFP initiatives achieved remarkable outcomes, significantly supporting accessibility to these vital food resources. In contrast, the remaining 4 programs, CSG, OPG, NSNP, and FFP, all demonstrated only limited support mainly due to low cash transfer values, inconsistent implementation, household demographic imbalances, and high living costs. This suggests that SPP policy currently lacks a comprehensive focus on nutritional sensitivity, which may not adequately meet the diverse dietary needs and health outcomes of the population it serves. This inadequate support contributes to a cycle of malnutrition, posing significant public health challenges within vulnerable communities.